Molecular mechanisms underlying cashmere quality differences between Jiangnan cashmere goats and Changthangi pashmina goats - Gong, Gao; Bi, Shijie; Liang, Xin; Ao, Yu; Xu, Feng; Sulaiman, Yiming (Frontiers in Veterinary Science, 2025)
Cashmere goats are excellent livestock breeds known for producing high-quality cashmere fibers from secondary hair follicles. In this study, we aimed to explore the key RNA molecules responsible for the differences in cashmere quality between Jiangnan cashmere goats (JNCG) and Changthangi pashmina goats (CPG). Skin transcriptomic data from the anagen, catagen, and telogen stages of hair follicle growth were retrieved from the SRA database for both JNCG and CPG. Bioinformatics analyses were conducted to identify key molecular differences underlying the variation in cashmere fiber quality. The results showed that there were 4,942 differentially expressed genes (DEGs) between JNCG and CPG through differential analysis, and the DEGs were mainly enriched in PI3K-Akt signaling pathway, Thermogenesis, ECM-receptor interaction in KEGG through functional enrichment analysis, and GO entries were mainly enriched in keratin filament, intermediate filament, keratinization. Twenty-four key candidate genes including IFG1, IGF1R, FGF5, FGF21, ND2, COX2, KRT10, KRT39, and KRT74 were further mined through pathways and entries. These genes play an important role in the development of secondary hair follicles and the formation of cashmere quality in cashmere goats, providing a theoretical basis for the genetic improvement of cashmere goats in the future.